1993
DOI: 10.1111/j.1365-2990.1993.tb00433.x
|View full text |Cite
|
Sign up to set email alerts
|

Virulent and avirulent strains of Semliki Forest virus show similar cell tropism for the murine central nervous system but differ in the severity and rate of induction of cytolytic damage

Abstract: The pathogenicity of the avirulent, demyelinating A7 strain of Semliki Forest virus (SFV) and the virulent SFV4 strain (derived from an infectious clone) for the central nervous system of adult BALB/c mice following intranasal infection was compared. The techniques used included immunocytochemistry using anti-SFV antibody and antibodies to cell markers, in situ hybridization (ISH) using a biotinylated cDNA probe specific for SFV, and immunocytochemistry/ISH double labelling. Whereas SFV4 was lethal at 4 days p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 26 publications
0
38
0
Order By: Relevance
“…SFV is a neuroinvasive and neurotropic virus that infects CNS neurons and oligodendrocytes (74,75). In adult C57BL/6 and BALB/c mice, the virus is for the most part cleared from the CNS by day 6 postinfection.…”
Section: Semliki Forest Virus (Sfv)mentioning
confidence: 99%
“…SFV is a neuroinvasive and neurotropic virus that infects CNS neurons and oligodendrocytes (74,75). In adult C57BL/6 and BALB/c mice, the virus is for the most part cleared from the CNS by day 6 postinfection.…”
Section: Semliki Forest Virus (Sfv)mentioning
confidence: 99%
“…However, infection with the avirulent variant strain (SFV-A7) is asymptomatic [9][10][11][12][13]. In a previous study, we observed an abortive infection of SFV-A7 on mouse splenic cells cultured in vitro [4]: viral protein was detected but no infectious virus released.…”
Section: Discussionmentioning
confidence: 96%
“…or intraperitoneally (i.p. ; Balluz et al, 1993). To verify infection, all surviving mice were challenged with a normally lethal dose of 10' p.f.u.…”
Section: Methodsmentioning
confidence: 99%
“…Growth and assay of the avirulent A7 strain of SFV in BHK-21 cells was as previously described (Balluz et al, 1993). The virulent SFV4 strain of SFV was produced by transcription and electroporation of the pSP6-SFV4 infectious clone of SFV (Glasgow et al, 1991).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation